Agronomic and nutritional assessment of cut-and-carry tropical grasses harvested at different intervals in Yurimaguas, Peruvian Amazon - Rupay T., Karen (2023)
Four tropical grasses were evaluated: Maralfalfa (Pennisetum violaceum Lam), Purple King grass (P. purpureum x P. typhoides), Elephant grass (Pennisetum purpureum, Schumach) and Guatemala grass (Tripsacum laxum, Nash) with two harvest intervals (45 and 70 days), using a factorial experiment with a randomized complete block design. The interaction pastures × cutting frequencies was significant (p<0.05) for the agronomic and nutritional characteristics. Purple King Grass and Guatemala harvested at 70 days produced higher dry matter yield (17.13 and 17.03 t ha-1, respectively) than Maralfalfa, Purple King Grass, Elephant grass, and Guatemala grass harvested at 45 days. Compared with other grasses, the Guatemala grass harvested at 45 days had the highest leaf: stem ratio (4.64). The highest average contents of protein (78.5 g kg-1) and phosphorus (1.22 g kg-1) were obtained at 45 days. It is concluded that the grasses harvested at 70 days showed their productive potential with a moderate nutritional value, which could be used to increase the yield per unit area. In addition, Guatemala grass could be used in studies with grazing animals due to its high leaf: stem ratio and moderate nutritional value.